FLEKSIBILITAS PERAN SUAMI-ISTERI PERSPEKTIF NATURAL LAW - Naseh, Ahmad M; Permatasari, Yovita Dyah; Wulandari, Yunita (UAS PRESS, 2025)
Religious norms determine the rights and obligations of husband and wife through sharia law. However, the reality of nature is different, many natural factors are sometimes not in harmony. For example, some obligations that a husband has are more perfect if carried out by the wife with the skills she has. Unlike other concrete legal norms, natural law is abstract and more flexible because humans can determine their own actions, which are good and bad without being dictated by existing norms. This study is a library research with a qualitative approach and uses content analysis methodology. This study aims to reveal the flexibility of the relationship between husband and wife in a household from a natural law perspective. This study produces the role of husband and wife in a household in the form of tasks that must be carried out by each. When the basic rules of the norms clash with reality, humans with the theory of natural law - as rational beings - carry out legal reasoning. The result is the flexibility of the role of husband and wife who complement each other, help each other in partnership. This flexible nature must also be proportional, in line with religious norms, rational, realistic, and carried out with full responsibility and commitment to building a family.